Hydration and acetylation of limonene. Supported heteropolyacids - Avila, Maria Cecilia (2008)
The limonene hydration and acetylation in liquid phase catalyzed by phosphotungstic and phosphomolybdic acid bulk and supported on silica and titanium dioxide were studied. The reaction was performed in a batch reactor in acetic acid at 40°C, with magnetic stirring of the reaction mixture. Reaction products were analyzed by gaseous chromatography with FID detector using a capillary column for separation of products. The identification of compounds was made with pattern terpenes and by gaseous chromatography with mass spectrometry. All catalysts tested result to be active in the hydration and acetylation reaction of limonene. Catalysts based on phophotungstic acid (HPW) produce larger amount of hydration and acetylation products than phosphomolybdic acid (HPMo) catalyst. Hydration products increase faster than isomerization products when the reaction time is increased. The structure of heteropolyacids and the presence of acid sites Bronsted and Lewis were determined by FTIR.